Compilers Without Borders - Thies, Bill; Amarasinghe, Saman; Ananthanarayanan, Vaishnavi; Cross, Andrew; Choudhary, Shubhranshu; Cutrell, Ed; D'Silva, Krittika; Gupta, Nakull; Ittan, Swati; Marathe, Meghana; O'Neill, Jacki; Pain, Paromita; et al. (2015)
Repurposing Paper, Plastic, and Household Devices as Computational Substrates Slide
POPL Off the Beaten Track, Mumbai, India